Mabel and Sam at home - Urban, Linda (Chronicle Books, 2018)
Mabel and her younger brother Sam approach their new home and the trauma of moving by turning it into an adventure, imagining they are sailors approaching a new land, tour guides exploring a museum, and finally astronauts in space